Bivalirudin vs. Heparin on Radial Artery Thrombosis during Transradial Coronary Intervention: An Optical Coherence Tomography Study - Zijing Liu; Guozhong Wang; Dan Niu; Yongxia Wu; Zixuan Li; Libin Zhang; Guohua Zhu; Qi Hua; Jincheng Guo (Journal of Interventional Cardiology)
Objectives. This study aimed to evaluate the antithrombotic efficacy between bivalirudin and unfractionated heparin (UFH) on radial artery thrombosis (RAT) during transradial coronary intervention (TRI) by optical coherence tomography (OCT). Methods and Results. We consecutively reviewed a total of 307 patients who underwent radial artery OCT inspection after TRI in our centre from October 2017 to January 2019; afterwards, 211 screened patients were divided into the UFH group (n = 144) and the bivalirudin group (n = 67) according to their anticoagulation strategy during TRI. The thrombosis in the radial artery was observed in 51 cases (24.17%) with a median thrombus volume of 0.054 mm3 (0.024, 0.334) and median thrombus score of 7 (4, 15). Thrombus occurred in 28 cases in the bivalirudin group with an incidence of 41.8%, which was significantly higher than that in the UFH group (n = 23, 16.0%, P<0.001). This difference was even more remarkable after propensity score matching (bivalirudin group n = 22, 42.3% vs. UHF group n = 11, 13.9%, P<0.001). Multivariate logistic analysis revealed that bivalirudin increased the RAT risk by 3.872 times (95% CI 2.006–8.354, P<0.001) after adjustment for the other predictors. Conclusion. In this present study, the use of bivalirudin was associated with a higher risk of RAT than UFH. It highlighted UFH should be a more considerable choice to prevent radial artery access thrombosis in TRI.